Application of Factor Analysis for Identification of Case Grouping in Mobile Telephony - de Sousa Oliveira, Juliane; Sousa Santos Neto, Agenor; Cesar Valandro Soares, Júlio (Revista Latino-Americana de Inovação e Engenharia de Produção, 2023)
With the opening of the market, competition in the Brazilian telephony sector has become fierce. In this new scenario, a fundamental issue emerges regarding to the evalu-ation of customers in order to the offer of services of providers. In this sense, the aim of this study is to apply factor analysis to describe a set of variables related to mobile consumer satis-faction by a smaller number of dimensions. The research was carried out with the help of SPSS software through which factor analysis was applied to create groupings of variables based on their relationship structure. The number of factors was chosen from the Kaiser criterion and the designated was the orthogonal rotation method - Varimax. The degree of explanation achieved by the two factors of the model corresponds to almost 69% of the variance of the original data. Thus, more than determining which indicators should be used to evaluate the results of mobile phone companies, factor analysis can be used to determine the importance in explaining the variables related to customer satisfaction that uses these services.